Graphene fabrication, characterizations, properties and applications - Zhu, Hongwei; Xu, Zhiping; Xie, Dan; Fang, Ying (Academic Press, 2018)
Graphene: Fabrication, Characterizations, Properties and Applications presents a comprehensive review of the current status of graphene, especially focused on synthesis, fundamental properties and future applications, aiming to giving a comprehensive reference for scientists, researchers and graduate students from various sectors. Graphene, a single atomic layer of carbon hexagons, has stimulated a lot of research interest owing to its unique structure and fascinating properties. The book is devoted to understanding graphene fundamentally yet comprehensively through a wide range of issues in the areas of materials science, chemistry, physics, electronics and biology. The book is an important resource of comprehensive knowledge pertinent to graphene and to related expanding areas. This valuable book will attract scientists, researchers and graduate students in physics and chemistry because it aims at providing all common knowledge of these communities including essential aspects of material synthesis and characterization, fundamental physical properties and detailed chapters focused on the most promising applications.--Provided by publisher.